(untitled) (Journal of the Bangladesh Agricultural University, 2024)
Both salinity and submergence are the global problems adversely affecting agricultural productivity in the coastal areas around the world. The current climate change made this situation more complex and is a threat to crop production. The present study was aiming to analyze genetic parameters among yield and yield related traits for ten rice genotypes in both saline and submergence condition. An experiment using a randomized complete block design (RCBD) and five different treatments viz., control, 9dSm-1 salinity + without submergence, 6dSm-1 salinity + complete submergence, normal water + complete submergence, 9dSm-1 salinity + complete submergence was conducted to estimate the genetic variability of ten rice genotypes. All the traits under this study reduced in both saline and submergence condition except days to flowering. In stressed condition, grain yield of all rice genotypes was reduced than no stressed condition. Considering all the treatments BRRI dhan47 showed higher stress tolerance followed by Binadhan-8, RC-191 and RC-221. In the present investigation, the highest genotypic coefficient of variation (GCV) and phenotypic coefficient of variation (PCV) were 21.42% and 30.16% observed for grain yield plant-1 (g), followed by total tillers hill-1 (11.92%, 17.42%) indicating that there is enough genetic variability for the traits. High heritability observed in the traits days to flowering followed by plant height and moderate heritability observed in grain yield plant-1 followed by filled grains panicle-1. This finding can be used for further breeding programs which helps in crop improvement under both saline and submergence condition. J Bangladesh Agril Univ 18(4): 993–1000, 2020 https://doi.org/10.5455/JBAU.129086